Personal Dispositions as a Determinant of Coping Strategy Selection in Difficult Circumstances - Khrystyna Stelmashchuk; Olga Moroz; Sofia Hrabovska; Tetyana Partyko (Insight: the psychological dimensions of society, 2023)
The purpose of the publication was to determine personal dispositions, which are basic traits and types of character accentuations that encourage a person to use specific coping strategies. Methods include theoretical analysis of scientific literature, mathematical and statistical data processing, and interpretive methods for explaining the investigated phenomena based on qualitative and quantitative research material analysis. Results. It was discovered that individuals with a high level of conscientiousness prefer planning strategies and assertive actions. People who lack goodwill and friendliness in their interpersonal relationships are prone to confrontational and avoidance coping. Individuals with a hyperthymic type of character accentuation, who show a tendency to confrontation, search for social support, problem-solving planning, positive reappraisal, assertive actions, antisocial actions, and do not show a tendency to avoidance, were found to have the most diverse repertoire of coping strategies. It was determined that the narrowest one was with rigid (tendency to confrontation) and pedantic accentuations (tendency to careful activities). It was proven that the selection of a constructive problemfocused coping strategy of planning when dealing with problems and an aggressive coping strategy depends on the hyperthymic type of accentuation. Discussion and conclusions. It was highlighted that the excitable type of accentuation is stimulated the selection of a nonconstructive problem-focused confrontation strategy and a non-constructive emotionally focused avoidance strategy. The emotional type of accentuation activates the selection of constructive emotionally focused strategies for finding social support, establishing social interactions, and positive reappraisal. It was summarized that basic personality traits and the type of character accentuation determine the predisposition to constructive/non-constructive problematic and emotionally oriented coping strategies. It was discovered that the choice of coping strategies depends on personal dispositions. The findings obtained allow for the prediction of a person's behavior in challenging situations, taking into consideration their personality traits and type of character accentuation. This may assist in the development of effective techniques of psychological assistance and behavioral correction.